MANAJEMEN TRANSFORMASI DIGITAL BERBASIS NILAI-NILAI KEISLAMAN: STRATEGI GURU DALAM PEMANFAATAN TEKNOLOGI PEMBELAJARAN DI PONDOK PESANTREN AL-FATTAH TEMBORO - Ridwan, Awaliyah Azzahrah; Adzkia, Hanina Najma; Aiska, Sabillah; Kamilah, Hana; Putri, Syifa Karimah; Yunus, Fikron; Syabani, Muhammad Rizki; Aulia, Rihlah Nur; Barnansyah, Rudi Muhammad (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The phenomenon of digital transformation requires educational institutions such as Islamic boarding schools to begin implementing technology into their institutional systems. However, in traditional Islamic boarding schools such as Al-Fattah Temboro, there are strict rules regarding the use of technology. This study aims to conduct an in-depth examination of how teachers use technology in teaching and manage digital change based on Islamic values at the Al-Fattah Temboro Islamic boarding school. This study employs a qualitative approach using field research methods. Data were collected through interviews with teachers involved in the implementation of digital technology. The data were then analyzed using the Miles and Huberman interactive model. The results indicate that the digital transformation at the Al-Fattah Temboro Islamic boarding school employs a selective digitization model grounded in Islamic values, limiting technology to offline computers, the web, and social media, while strictly prohibiting the use of smartphones through firm sanctions. This approach has dual implications: it successfully maintains the students’ spiritual and academic focus but risks leaving them technologically unprepared after graduation. This study offers theoretical and practical contributions in the form of a safe digital transition model to ensure the sustainability of traditional Islamic education amid the tide of modernization.